Electrochemical Performance of Graphitic Multi‐walled Carbon Nanotubes with Different Aspect Ratios as Cathode Materials for Aluminum‐ion Batteries. Issue 8 (3rd August 2020) - Hou, Lixue; Cao, Haining; Han, Mei; Lv, Zichuan; Zhou, Shuai; Chen, Hui; Du, Huiping; Cai, Mian; Zhou, Yue; Meng, Chao; Bian, Yinghui; Lin, Meng‐Chang
Abstract: Graphitic multi‐walled carbon nanotubes (MWCNTs) can function as high‐performance cathode materials for rechargeable Al‐ion batteries with well‐defined discharging plateaus and reasonable charge/discharge C‐rates. However, the main intercalation/deintercalation or adsorption/desorption path of AlCl4 − anions into or onto G‐MWCNTs has not been elucidated. Herein, we used battery cells comprised of G‐MWCNTs with different aspect ratios, Al metal, and AlCl3 /1‐ethyl‐3‐methylimidazolium chloride ionic liquid as the cathode, anode, and electrolyte, respectively. The electrochemical performance of the Al||G‐MWCNT cell increased as the aspect ratio of the G‐MWCNT cathode increased (i. e., longer and thinner). The degree of defects of the G‐MWCNTs was similar (0.15–0.22); hence, the results confirm that the main and alternate paths for the AlCl4 − intercalation/de‐intercalation or adsorption/desorption into/from or onto/from the G‐MWCNT are the basal and edge planes, respectively. The step‐like structures of defects on the basal plane provide the main reaction site for AlCl4 − anions. Abstract : A matter of ratios : During the charging process, it is proposed that the main pathway for the AlCl4 − intercalation or adsorption into/onto the MWCNT is the basal plane with defects, and the alternate pathway is the edge plane at both ends of the MWCNT. The thinner the MWCNT wall and the longer the length, the easier the intercalation/deintercalation and/or adsorption/desorption of AlCl4 − .